A prospective study of predictors of metabolic syndrome in women with polycystic ovary syndrome - Gupta, Jubie; Minhas, Santosh; Jindal, Monika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Polycystic ovary syndrome (PCOS) is a well-known gynecological hormonal imbalance. The consequences of PCOS pose a substantial risk for the development of metabolic and cardiovascular abnormalities similar to those that make up metabolic syndrome (MBS). Therefore, there was a need to identify predictors for MBS in PCOS subjects and study their strength of association. Methods: A prospective observational study was carried on 100 PCOS subjects for having features of MBS. MBS was diagnosed by National cholesterol education program’s adult treatment panel III 2001 criteria. Student’s independent t test, Chi square test and Fisher’s exact test were used for statistical analysis. Results: The present study estimated the prevalence of MBS in women with PCOS to be 31%. MBS in PCOS was more prevalent in non-vegetarians (51.6%). The individual components of MBS criterion had a statistically significant p value (p=0.001 to 0.008) for development of PCOS. Raised levels of triglycerides, fasting blood sugars and fasting insulin tests were related directly to MBS development, with statistically significant p values (<0.001, <0.001 and 0.005), respectively. Conclusions: Women with PCOS have a high prevalence of MBS and its individual components, particularly raised laboratory values of triglycerides, fasting blood sugars and fasting insulin. MBS in PCOS women is associated with advancing age and obesity.